Karakterisik Granul Dan Tablet Propranolol Hidroklorida Dengan Metode Granulasi Peleburan - Nugrahani, Ilma; Rahmat, Hasan; Djajadisastra, Joshita (UI Scholars Hub, 2005)
The effect of carnauba wax consentration to pharmacotechnical characteristics on the granules and tablets that made by hot melt granulation method have been studied. Fomula I? V with composition : 10, 20, 30, 40, and 50% w/w carnauba wax, propranolol hydrochloride 60 mg/tablet, and lactose to the 340 mg was mixed and melted, and than sieved to the mesh 16 siever. The granules were evaluated and lubricated by 1% magnesium stearat and 2% talcum. Then it were compressed into tablet which each weight was 350 mg and the tablets were evaluated. The results showed that hot melt granulatin form granules and tablets that acceptable pharmacotechnical properties.